Endothelial Progenitor Cells: Therapeutic Target for Cardiovascular Diseases - Takashi Umemura; Yukihito Higashi (Elsevier, 2008)
Circulating endothelial progenitor cells (EPCs) derived from bone marrow were isolated for the first time in 1997 and characterized. Recent evidence has indicated that EPCs contribute to reendothelialization of injured vessels as well as neovascularization of ischemic lesions and that a decrease in the number of EPCs is an independent predictor of morbidity and mortality of cardiovascular diseases. These finding suggest that EPCs play a major role in the pathogenesis of atherosclerosis and cardiovascular diseases. Interestingly, the number and function of EPCs are regulated by not only various kinds of angiogenic cytokines and cardiovascular risk factors per se but also some interventions, including lifestyle modification (aerobic exercise, body weight loss, and smoking cessation) and pharmacological therapy (e.g., renin-angiotensin system inhibitor, statin, and erythropoietin). It is thought that regulation of the number and function of EPCs directly influences the maintenance and development of atherosclerosis. Therefore, it is clinically important to estimate the degree of EPC bioactivity and to increase the EPC bioactivity by appropriate interventions. In this review, we focus on the relationship between EPCs and cardiovascular risk factors and the role of EPCs in cardiovascular diseases. Keywords:: endothelial progenitor cell, cardiovascular disease, cardiovascular risk factor, nitric oxide